Traditional Beliefs, Practices, and Migration: A Risk to Malaria Transmission in Rural Nepal. - Awasthi, Kiran Raj; Jancey, Jonine; Clements, Archie CA; Sah, Rohit Kumar; Koirala, Madan Prasad; Chalise, Binaya; Leavy, Justine (MDPI, 2022)
The study aimed to explore sociocultural factors influencing the risk of malaria and practices and beliefs towards malaria prevention, transmission and treatment in a remote village in Khatyad Rural Municipality (KRM) of Nepal. A sequential exploratory mixed methods approach was used. Qualitative data were collected through 25 one-on-one, in-depth interviews followed by a face-to-face household survey (n = 218) among people from a village in KRM believed to have a high risk of malaria. Traditional practices such as Chhaupadi requiring the seclusion of women during menstruation and post-partum, transhumance, and reliance on traditional healers for the management of malaria were common practices in the village. The household survey found 98.1% of women faced menstrual exile either inside the house or in a separate hut, with 64.2% not having access to Long-lasting Insecticidal Nets (LLINs). Hardships and economic constraints compelled villagers to migrate seasonally for work to malaria-endemic areas in India, thereby exposing themselves to the risk of malaria. Persistent traditional beliefs and seasonal migration could threaten the elimination goals set by the national malaria program.